Adoption of near field communication in S-Library application for information science. Issue 11 (9th November 2015) - YUSOF, MOHD KAMIR; Abel, Andrew; Saman, Md Yazid; Abdul Rahman, Mohd Nordin
Abstract : Purpose: – The purpose of this paper is to first review the implementation of automatic identification and data capture) technologies in library/information science, focusing on barcode technology, radio frequency identification (RFID) and near field communication (NFC). This paper then presents S-Library, a new android-based application, to enable users to perform a wide range of information science-related transactions, such as borrowing, searching, returning and viewing transaction records. Design/methodology/approach: – This paper presents the design process and the database and software components. For analysis, the authors used application testing, and also usability testing, with a questionnaire distributed to 343 users. Findings: – The implementation of NFC technology means that S-Library has a number of technical advantages over other approaches. It was also shown with user acceptance testing that there was a high degree of user satisfaction with S-Library. Research limitations/implications: – Although the findings combine technical assessment and usability testing and are extremely positive, further user evaluation could be performed. In addition, S-Library does not currently read existing RFID tags, which would improve the application further. Practical implications: – The system proposed here shows that S-Library is a feasible approach taken to improve the library transaction experience and that it can replace and improve upon older technologies. Originality/value: – This paper provides a first successful demonstration of a functioning and tested android and NFC-based library transaction system and shows that this approach generates a high degree of user reliability.